UPAYA MENCEGAH KEKERASAN SEKSUAL MELALUI PENDIDIKAN KELUARGA PADA PROGRAM BINA KELUARGA BALITA - Dini Rakhmawati; Desi Maulia; Yovitha Yuliejatiningsih (Jurnal Bimbingan dan Konseling Terapan, 2020)
The number of violence against children continues to increase every year. The prevention to sexual violence toward children should involve the community. Sexual education should be started through family. Parents teach their toddler about the body, how to respect their body, and how to protect their self. Bina Keluarga Balita as a national program to educate the community, will teach society to prevent sexual violence toward children continuously. The study used the Research and Development approach. The population of the study involved mothers at the Posyandu in Kecamatan Gunungpati which were divided into 16 sub-districts. The research sample was residents from the sub-districs who had low socio-economic and had children aged 2 - 6 years. Research uses purposive sampling technique. Methods of collecting data using scale instruments, questionnaires, achievement tests and interviews. Data analysis used a different test to compare the attitudes and knowledge of mothers to sexual violence in children.The results of testing in small groups and groups are broader, both of which show an increasement in attitudes and knowledge and coping with maternal stress on sexual violence toward children after training in Bina Keluarga Balita. This proves that family education through a toddler family development program is effective in increasing attitudes and knowledge and coping with maternal stress on sexual violence toward children, and this program can be recommended as an effort to prevent sexual violence toward children in community.